Wind Potential in the Santa Cruz de Succhabamba province - Cajamarca department 2023 - Carrasco Díaz, Juan Deini (2023)
Faced with the worrying curve of considerable slope that represents the evolution of greenhouse gas emissions in recent decades, this research is committed to the use and consumption of energy from non-conventional sources, which is the seventh Development Goal. Sustainable Development (SDG) for which, in contribution to its compliance, it was sought to quantify the wind potential present on the crest of the Cotorumi hill located in the district of Santa Cruz de Succhabamba, province of Santa Cruz, department of Cajamarca - Peru. It was decided to apply the quantitative approach with a non-experimental design. From the Weibull statistical distribution, the satellite data of wind speed at 50 meters of height of the last decade were analyzed, finding the presence of a potential of 94.48 Watts for each square meter that, taking into account the power coefficient of wind turbines commercial with horizontal axis, the extractable power would approximate the value of 37.8 Watts per square meter. The average energy consumption of the province of Santa Cruz de Succhabamba would be easily covered by a horizontal axis wind turbine that has a swept area greater than 5,767.7 square meters.